Archaeal Shikimate Kinase, a New Member of the GHMP-Kinase Family - Daugherty, Matthew (American Society for Microbiology, 2001)
Shikimate kinase (EC 2.7.1.71) is a committed enzyme in the seven-step biosynthesis of chorismate, a major precursor of aromatic amino acids and many other aromatic compounds. Genes for all enzymes of the chorismate pathway except shikimate kinase are found in archaeal genomes by sequence homology to their bacterial counterparts. In this study, a conserved archaeal gene (gi|1500322 in Methanococcus jannaschii) was identified as the best candidate for the missing shikimate kinase gene by the analysis of chromosomal clustering of chorismate biosynthetic genes. The encoded hypothetical protein, with no sequence similarity to bacterial and eukaryotic shikimate kinases, is distantly related to homoserine kinases (EC 2.7.1.39) of the GHMP-kinase superfamily. The latter functionality in M. jannaschii is assigned to another gene (gi|1591748), in agreement with sequence similarity and chromosomal clustering analysis. Both archaeal proteins, overexpressed in Escherichia coli and purified to homogeneity, displayed activity of the predicted type, with steady-state kinetic parameters similar to those of the corresponding bacterial kinases: K(m,shikimate) = 414 ± 33 μM, K(m,ATP) = 48 ± 4 μM, and k(cat) = 57 ± 2 s(−1) for the predicted shikimate kinase and K(m,homoserine) = 188 ± 37 μM, K(m,ATP) = 101 ± 7 μM, and k(cat) = 28 ± 1 s(−1) for the homoserine kinase. No overlapping activity could be detected between shikimate kinase and homoserine kinase, both revealing a >1,000-fold preference for their own specific substrates. The case of archaeal shikimate kinase illustrates the efficacy of techniques based on reconstruction of metabolism from genomic data and analysis of gene clustering on chromosomes in finding missing genes.